Extinction recall of fear memories formed before stress is not affected despite higher theta activity in the amygdala. - Rahman, Mohammed Mostafizur; Shukla, Ashutosh; Chattarji, Sumantra (Elife, 2018)
Stress is known to exert its detrimental effects not only by enhancing fear, but also by impairing its extinction. However, in earlier studies stress exposure preceded both processes. Thus, compared to unstressed animals, stressed animals had to extinguish fear memories that were strengthened by prior exposure to stress. Here, we dissociate the two processes to examine if stress specifically impairs the acquisition and recall of fear extinction. Strikingly, when fear memories were formed before stress exposure, thereby allowing animals to initiate extinction from comparable levels of fear, recall of fear extinction was unaffected. Despite this, we observed a persistent increase in theta activity in the BLA. Theta activity in the mPFC, by contrast, was normal. Stress also disrupted mPFC-BLA theta-frequency synchrony and directional coupling. Thus, in the absence of the fear-enhancing effects of stress, the expression of fear during and after extinction reflects normal regulation of theta activity in the mPFC, not theta hyperactivity in the amygdala.
Keywords: Amygdala; Animals; Extinction, Psychological; Fear; Male; Memory; Mental Recall; Prefrontal Cortex; Rats, Sprague-Dawley; Stress, Physiological; Theta Rhythm